Arterial stiffness and cardiovascular events: The Framingham Heart Study - Mitchell, Gary F. (2010)
BACKGROUND: Various measures of arterial stiffness and wave reflection have been proposed as cardiovascular risk markers. Prior studies have not assessed relations of a comprehensive panel of stiffness measures to prognosis in the community. METHODS AND RESULTS: We used proportional hazards models to analyze first-onset major cardiovascular disease (CVD) events (myocardial infarction, unstable angina, heart failure or stroke) in relation to arterial stiffness (pulse wave velocity, PWV), wave reflection (augmentation index, carotid-brachial pressure amplification) and central pulse pressure in 2232 participants (mean age 63 years, 58% women) in the Framingham Heart Study. During median follow-up of 7.8 (range 0.2 to 8.9) years, 151 of 2232 participants (6.8%) had an event. In multivariable models adjusting for age, sex, systolic blood pressure, use of antihypertensive therapy, total and HDL cholesterol concentrations, smoking and presence of diabetes, higher aortic PWV was associated with a 48% increase in CVD risk (95% CI, 1.16 to 1.91 per SD, P=0.002). After adding PWV to a standard risk factor model, integrated discrimination improvement was 0.7% (95% CI, 0.05 to 1.3%, P<0.05). In contrast, augmentation index, central pulse pressure and pulse pressure amplification were not related to CVD outcomes in multivariable models. CONCLUSIONS: Higher aortic stiffness assessed by PWV is associated with increased risk for a first cardiovascular event. Aortic PWV improves risk prediction when added to standard risk factors and may represent a valuable biomarker of CVD risk in the community.